The teacher’s self-constructed approaches to collaborate with newcomer parents in the Norwegian elementary reception class - Norozi, Sultana Ali; Moen, Torill (Frontiers in Education, 2022)
In Norway, newly arrived immigrant children often start their schooling in special groups called reception classes. This study aims to examine one Norwegian reception teacher’s perceptions and practices of collaborating with the children’s parents. The empirical analyses are based on a qualitative approach with interviews and video observations of the teacher. Affirming earlier research about parent–teacher collaboration in Norway, the study shows that the teacher has developed her own practices of parent–teacher collaboration. Contradicting earlier research, the findings highlight that despite challenges, the teacher experiences collaboration with newcomer parents positively. This article presents activities the teacher engages in within and outside the classroom to foster mutual learning and parental involvement. In the discussion, the teacher’s approaches are not judged as right or wrong, perfect or imperfect, but rather appreciated as self-constructed and self-initiated approaches to collaborating with newcomer parents. The main result is that despite challenges, if the teacher appears to be motivated and has positive/pluralistic perceptions of immigrant pupils and their parents, then s/he finds ways to collaborate with newcomer parents. This article concludes with teachers’ practice recommendations for schools and some directions for future research.